Avian Stress-Related Transcriptome and Selenotranscriptome: Role during Exposure to Heavy Metals and Heat Stress - Isidoros Seremelis; Georgios P. Danezis; Athanasios C. Pappas; Evangelos Zoidis; Kostas Fegeros (MDPI AG, 2019)
Selenium, through incorporation into selenoproteins, is one of the key elements of the antioxidant system. Over the past few years there has been increased interest in exploring those molecular mechanisms in chicken, responsible for the development of this protection system. In more detail, Cd/Pb poisoning and heat stress increase oxidation, mRNA levels of inflammatory proteins, and apoptotic proteins. Selenium seems to enhance the antioxidant status and alleviates these effects via upregulation of antioxidant proteins and other molecular effects. In this review, we analyze avian transcriptome key elements with particular emphasis on interactions with heavy metals and on relation to heat stress.